Coach - player - physiotherapist - Claes, A. (Medicine and Science in Tennis, 2008)
About the relationship between coach, player and physiotherapist, which is critical to success, not only in terms of high quality health care and prevention of injuries, but also in terms of supporting the player in their development. In conclusion, high quality medical care for elite players requires teamwork of exceptional caliber. It begins with an outstanding relationship between the player, parents and support staff and at its best ensures that communication, knowledge and skill come together in seamless harmony.